60. NUTRITION STATUS OF CHILDREN UNDER 5 YEARS OLD IN NGA NAM DISTRICT, SOC TRANG PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Background: Proper nutrition plays a crucial role in the comprehensive physical and cognitive development of children, contributing to the enhancement of a nation's overall stature and intelligence. At present, there has been no study conducted on the nutritional status of children under five years old in Nga Nam town, Soc Trang province.Objective: Determine the rate and describe the nutritional status of children under 5 years old in Nga Nam town, Soc Trang province in 2024.Method: A cross-sectional study was conducted on 300 children under 5 years of age, randomly selected from the sampling list, along with their 300 corresponding mothers. Data were collected using a structured questionnaire and anthropometric measurements of the children.Results: The study found that 54.3% of the children were male and 45.7% were female. The prevalence of malnutrition was 31.7%, including 14.3% stunting, 10.0% underweight, and 7.3% wasting. The prevalence of overweight and obesity was 9.0%.Conclusion: Nutrition education for caregivers should be strengthened to help improve the nutritional status of young children.
Keywords: Stunting; Underweight; Wasting